ANALISIS PENGETAHUAN MASYARAKAT RT 01 RW 04 DESA LURAGUNG LANDEUH KECAMATAN LURAGUNG KABUPATEN KUNINGAN MENGENAI OBAT BEBAS TERBATAS DAN OBAT KERAS - Supriyani, Cucu; Sari, Liska Marlinda (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2019)
Lack of public knowledge about complete information of medicines can cause errors. Information about drugs would prevent knowledge and understanding in drugs use. This research was done at determine the level of public knowledge about free and limited drugs. This research was conducted in RT 01 RW 04 in Pahing Hamlet, Luragung Landeuh in june-july 2019. This type of research used a survey method which was analyzed descriptively. Data collection by distributing questionnaires to 52 respondents. The questionnaire used was a guttman scale type quesionare and was made in the form of a checklist (Ã¢Ë†Å¡) with 2 answer options. The result of this of this study indicate that the knowladge of the community of RT 01 RW 04 in Pahing Hamlet, Luragung Landeuh village regarding limited free drugs and Hard drugs includes the less knowledge category (55.52%)